Myoepithelioma of the Parotid Gland: CT Imaging Findings - Wang, S.; Shi, H.; Wang, L.; Yu, Q. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Myoepitheliomas (MEs) are rare tumors of the parotid gland. Only a few case reports describing CT imaging features of ME have been published. The aim of this study was to describe and characterize the CT findings of MEs of the parotid gland.MATERIALS AND METHODS: We retrospectively reviewed CT images of ME with pathologic correlation in 10 cases (4 men and 6 women; age range, 30–70 years) collected between August 2003 and October 2007 from our pathologic database. All of the CT images were retrospectively evaluated with respect to the location, size, marginal morphology, enhancement, and enhancement pattern by 2 experienced radiologists.RESULTS: Nine tumors were located in the superficial lobe of the parotid gland, and 1 was located in the tail of parotid gland. All of the tumors abut on the capsule of the gland. Nine tumors had well-defined margins with lobulations in 5 patients. Two cases showed homogenous enhancement. In the other 8 cases, the enhancement was inhomogeneous because of enhancing nodules and nonenhancing areas of linear bands, slitlike-shaped or of cystic configuration.CONCLUSION: CT imaging findings of MEs were well circumscribed, enhancing the mass lesion with smooth or lobulated margins, located chiefly in the superficial lobe and abutted on the capsule of the gland. They may contain enhancing nodules and nonenhancing areas of linear bands, slitlike-shaped or of cystic configuration. Although MEs are a rarity, they should be suspected when a tumor shows all of the characteristics noted here.